2018
DOI: 10.1016/j.jad.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Association between parental marital conflict and Internet addiction: A moderated mediation analysis

Abstract: This study helps to elucidate the mechanism underlying the association between parental marital conflict and Internet addiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 41 publications
2
30
1
Order By: Relevance
“…Moreover, the second part of the mediation chain also highlights the previously supported relations between depression and adolescent's IA (Zhao et al, 2017;Gao et al, 2018). Specifically, depressed adolescents tend to have more negative self-evaluations and experience stronger feelings of worthlessness (Yen et al, 2019).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Moreover, the second part of the mediation chain also highlights the previously supported relations between depression and adolescent's IA (Zhao et al, 2017;Gao et al, 2018). Specifically, depressed adolescents tend to have more negative self-evaluations and experience stronger feelings of worthlessness (Yen et al, 2019).…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, it is reasonable to assume that psychological disorders such as depression may mediate the relationship between cybervictimization and adolescents' IA. Consistent with this theoretical framework, several empirical research have demonstrated this view (Zhao et al, 2017;Gao et al, 2018;Sela et al, 2020). For example, a study of 10,000 Chinese vocational school students showed that depression significantly mediated the relationship between negative life events and IA (Zhao et al, 2017).…”
Section: The Mediating Role Of Depressionmentioning
confidence: 75%
“…We used a Korean version of the CPIC which demonstrated good reliability and validity for assessing parental marital conflict at baseline [23]. Although the full version of the CPIC consists of 49 questions, we only adopted the characters of conflict subscale, which contained 19 items [24] and included four dimensions: conflict frequency (four questions), conflict intensity (five questions), (lack of) conflict resolution (seven questions), and stability of conflict (three questions) to measure children's perception of their parents' marital conflicts by conducting a confirmatory factor analysis. The response format was a five-point Likert scale ranging from 1 (never) to 5 (always).…”
Section: Parental Marital Conflictmentioning
confidence: 99%
“…Parental marital conflict was measured using the Children's Perception of Intraparental Conflict Scale (CPIC), which was developed by Grych, Seid and Fincham (1992) 22 at baseline. Although the full version of the CPIC consists of 49 questions, we only adopted the characters of conflict subscale, which contained 19 items 23 and included four dimensions: conflict frequency (four questions), conflict intensity (five questions), (lack of) conflict resolution (seven questions), and stability of conflict (three questions) to measure children's perception of their parents' marital conflicts by conducting a confirmatory factor analysis. The response format was a five-point Likert scale ranging from 1 (never) to 5 (always).…”
Section: Parental Marital Conflictmentioning
confidence: 99%